Single cell and genetic analyses reveal conserved populations and signaling mechanisms of gastrointestinal stromal niches - Ji-Eun Kim (Nature Portfolio, 2020)
Wnt signals for intestinal stem cell self-renewal originate from the stroma and Paneth cells, but the source in stomach is unclear. Here the authors identify a conserved population of stromal cells adjacent to stomach epithelia where Gli2 activates Wnt ligands to promote gastrointestinal regeneration and development.